Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Antiplasmid activity of 1 `-acetoxychavicol acetate from alpinia galanga against multi-drug resistant bacteria - Latha, C.; Shriram, Varsha D.; Jahagirdar, Sheetal S.; Dhakephalkar, Prashant K.; Rojatkar, Supada R. (Journal of Ethnopharmacology, 2009)
Ethnopharmacological relevance: Alpinia galanga (L.) Swartz is traditionally used in the treatment of various ailments across India, China, and Southeast Asian countries. In India it is a reputed drug in indigenous system of medicine and largely used as antibacterial and antiseptic. In southern India the rhizomes has been used as a domestic remedy against bacterial infections. Aim of the study: To identify a potential antiplasmid compound from Alpinia galanga against multi-drug resistant bacteria. Materials and methods: The crude rhizome extract of Alpinia galanga was prepared in acetone. Antibacterial activity was checked by MIC and antiplasmid activity was checked by SIC. The principal compound responsible for the antiplasmid activity, in the crude extract, was identified by bioassay guided fractionation using hexane-acetone. Antibiotic resistance profile of plasmid harboring strains and plasmid cured strains was determined by disc diffusion method. Results: The crude acetone extract of the rhizomes of Alpinia galanga exhibited antiplasmid activity against Salmonella typhi, Escherichia coli and vancomycin resistant Enterococcus faecalis with an efficiency of 92%, 82% and 8% respectively at 400 mu g/ml SIC. The principal compound responsible for the activity was identified as 1'-acetoxychavicol acetate. 1'-Acetoxychavicol acetate demonstrated the ability to cure plasmid encoded antibiotic resistance in various multi-drug resistant bacterial strains of clinical isolates such as Enterococcus faecalis, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli and Bacillus cereus with curing efficiency of 66%, 75%, 70%, 32% and 6% respectively at SIC of 400-800 mu g/ml. Conclusion: 1'-Acetoxychavicol acetate mediated R-plasmid curing significantly reduced the minimal inhibitory concentration of antibiotics required to inhibit growth of bacteria, thus making the antibiotic treatment more effective. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: 1 `-Acetoxychavicol acetate; Alpinia galanga; Antibiotic resistance; Antiplasmid

Antibacterial & antiplasmid activities of Helicteres isora L. - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Dhakephalkar, Prashant K.; Rojatkar, Supada; Shitole, Mahadeo G. (Indian Journal of Medical Research, 2010)
Background & objectives: The multiple drug resistance (MDR) is a serious health problem and major challenge to the global drug discovery programmes. Most of the genetic determinants that confer resistance to antibiotics are located on R-plasmids in bacteria. The present investigation was undertaken to investigate the ability of organic extract of the fruits of Helicteres isora to cure R-plasmids from certain clinical isolates. Methods: Active fractions demonstrating antibacterial and antiplasmid activities were isolated from the acetone extracts of shade dried fruits of H. isora by bioassay guided fractionation. Minimal inhibitory concentration (MIC) of antibiotics and organic extracts was determined by agar dilution method. Plasmid curing activity of organic fractions was determined by evaluating the ability of bacterial colonies (pre treated with organic fraction for 18 h) to grow in the presence of antibiotics. The physical loss of plasmid DNA in the cured derivatives was further confirmed by agarose gel electrophoresis. Results: The active fraction did not inhibit the growth of either the clinical isolates or the strains harbouring reference plasmids even at a concentration of 400 mu g/ml. However, the same fraction could cure plasmids from Enterococcus faecalis, Escherichia coli, Bacillus cereus and E. coli (RP4) at curing efficiencies of 14, 26, 22 and 2 per cent respectively. The active fraction mediated plasmid curing resulted in the subsequent loss of antibiotic resistance encoded in the plasmids as revealed by antibiotic resistance profile of cured strains. The physical loss of plasmid was also confirmed by agarose gel electrophoresis. Interpretation & conclusions: The active fraction of acetone extract of H. isora fruits cured R-plasmids from Gram-positive and Gram-negative clinical isolates as well as reference strains. Such plasmid loss reversed the multiple antibiotic resistance in cured derivatives making them sensitive to low concentrations of antibiotics. Acetone fractions of H. isora may be a source to develop antiplasmid agents of natural origin to contain the development and spread of plasmid borne multiple antibiotic resistance.
Keywords: antibacterial activity; Antibiotic resistance; antiplasmid activity; Helicteres isora; multiple drug resistance; plasmid-curing